Apdt Activity of New Water Soluble Phenalenone Derivatives with Shifted Uv–Vis Absorption - Vasquez-Martinez, y; Silva-Molina, C; Silva-Molina, C; Sandoval-Altamirano, C (Elsevier B.V., 2025)
Antibacterial therapy is one of the most important medical developments of the 20th century, but several decades of antibiotic misuse and abuse have created a health emergency. Antibiotics resistance and ineffectiveness have spread through the community, threatening the enormous gains made by the availability of therapies. The emergence of drug-resistant infections has encouraged research community to develop new mechanisms against bacterial infections, mainly focused on multi-target strategies like “Antibacterial Photodynamic Therapy (aPDT)”, where singlet oxygen (an excited state of oxygen) is able to oxidize a wide range of biomolecules including proteins, lipids and nucleic acids, leading to bacterial death. Singlet oxygen oxidative damage in aqueous media is restricted by its short diffusion range, around 150 nm. It is crucial to increase photosensitizer solubility in aqueous media keeping the capability of partition in apolar media (like membranes). We have previously demonstrated that an alkoxy substitution in position 6 of phenalenone scaffold (6-alkoxy-PNF) promotes a bathochromic shift of UV–Vis absorption when compared to clean phenalenone, (with maximum absorption wavelength centered at around 430–450 nm depending on the solvent). Their quantum yields of singlet oxygen generation remained high, in most media. To take advantage of the photo-physical properties of 6-alkoxy-PNF framework, increase solubility in water and promote attractive electrostatic interaction on the bacterial surface, a trimethylammonium group was introduced in the molecule. Moreover, depending on the length of methylene chain included, hydrophilic lipophilic balance of molecules can be tuned. This substitution through a methylene linker would maintain distance from the 6-alkoxy-PNF, keeps almost unchanged their visible absorption bands (displaced to the red) and their singlet oxygen generation capacity. Their ability to generate singlet oxygen and hence inactivate bacteria was tested. Our results show that the behavior of this family of compounds is dependent on the length of the alkyl chain, particularly in micro-heterogeneous systems. Synergic effect can be attributed to 12C surfactant associated with antimicrobial surfactant ability and singlet oxygen generation. © 2025 Elsevier B.V.